The 2017 national survey of online learning in Canadian post-secondary education: methodology and results - Bates, Tony (International Journal of Educational Technology in Higher Education, 2018)
Canada has a long history of online and distance education, but until 2017 there had been no comprehensive national data on online enrolments in both the university and college sectors. However, in 2017 a team of independent Canadian researchers, working in collaboration with the Babson Survey Research Group and WCET in the USA, raised the funding and conducted a national survey of online learning in all public post-secondary institutions in Canada. The results from the survey are presented and discussed, as well as plans for further studies in the future.